Adaptation to a fat-rich diet: effects on endurance performance in humans - Helge, J. W. (Sports Medicine, 2000)
The focus of this review is on studies where dietary fat content was manipulated to investigate the potential ergogenic effect of fat loading on endurance exercise performance. Adaptation to a fat-rich diet is influenced by several factors, of which the duration of the adaptation period, the exercise intensity of the performance test and the content of fat and carbohydrate in the experimental diet are the most important. Evidence is presented that short term adaptation, < 6 days, to a fat-rich diet is detrimental to exercise performance. When adaptation to a fat-rich diet was performed over longer periods, studies where performance was tested at moderate intensity, 60 to 80% of maximal oxygen uptake, demonstrate either no difference or an attenuated performance after consumption of a fat-rich compared with a carbohydrate-rich diet. When performance was measured at high intensity after a longer period of adaptation, it was at best maintained, but in most cases attenuated, compared with consuming a carbohydrate-rich diet. Furthermore, evidence is presented that adaptation to a fat-rich diet leads to an increased capacity of the fat oxidative system and an enhancement of the fat supply and subsequently the amount of fat oxidised during exercise. However, in most cases muscle glycogen storage is compromised, and although muscle glycogen breakdown is diminished to a certain extent, this is probably part of the explanation for the lack of performance enhancement after adaptation to a fat-rich diet.